2014
DOI: 10.1136/jech-2014-204184
|View full text |Cite
|
Sign up to set email alerts
|

Negative socioeconomic changes and mental disorders: a longitudinal study

Abstract: BackgroundThere is increasing interest on whether the current global economic uncertainties have an influence on the population's mental health. In this paper, we examined the association of negative socioeconomic changes, job loss and household income reductions with incident mental disorders. The moderating effect of gender was assessed.MethodsData come from the Netherlands Mental Health Survey and Incidence Study-2 (NEMESIS-2), a representative population-based, longitudinal study. Individuals with a paid j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
4
36
1
4
Order By: Relevance
“…In this context, our findings support the hypothesis that the worsening of socioeconomic conditions observed during this period could have contributed to mental health decline [19], particularly amongst immigrants [34], as our data refer to years just before and after global economic crisis. Conversely to what was observed in Spain, a country with similar socioeconomic characteristics as Italy [35], we did not find any increase in differences in poor self-perceived mental health amongst immigrant women compared with natives.…”
Section: Discussionsupporting
confidence: 87%
“…In this context, our findings support the hypothesis that the worsening of socioeconomic conditions observed during this period could have contributed to mental health decline [19], particularly amongst immigrants [34], as our data refer to years just before and after global economic crisis. Conversely to what was observed in Spain, a country with similar socioeconomic characteristics as Italy [35], we did not find any increase in differences in poor self-perceived mental health amongst immigrant women compared with natives.…”
Section: Discussionsupporting
confidence: 87%
“…The situation is likely to worsen now as Brazil undergoes a harsh economic recession; it has been shown that economic crises that lead to job losses and income reductions, even in rich countries, have an important negative impact on mental health [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Job loss is one of those critical life events that is frequent and can be regarded as example constellation for AjD. Research has shown its negative impact on physical health (Gallo et al, 2004), health behaviour (Gallo, Bradley, Siegel, & Kasl, 2001), and mental health (Ziersch, Baum, Woodman, Newman, & Jolley, 2014), in particular the onset of depressive symptoms and anxiety reactions (Barbaglia, Have, Dorsselaer, Alonso, & De Graaf, 2014). …”
Section: Socio-interpersonal Model Of Stress-response Syndromesmentioning
confidence: 99%